Ultrasonic dissection versus electrocautery dissection in laparoscopic cholecystectomy for acute cholecystitis: a randomized controlled trial (SONOCHOL-trial) - My Blohm; Gabriel Sandblom; Lars Enochsson; Yücel Cengiz; Haytham Bayadsi; Joakim Hennings; Angelica Diaz Pannes; Erik Stenberg; Kerstin Bewö; Johanna Österberg (World Journal of Emergency Surgery)
Abstract Background Laparoscopic cholecystectomy with ultrasonic dissection presents a compelling alternative to conventional electrocautery. The evidence for elective cholecystectomy supports the adoption of ultrasonic dissection, citing advantages such as reduced operating time, diminished bleeding, shorter hospital stays and decreased postoperative pain and nausea. However, the efficacy of this procedure in emergency surgery and patients diagnosed with acute cholecystitis remains uncertain. The aim of this study was to compare outcomes of electrocautery and ultrasonic dissection in patients with acute cholecystitis. Methods A randomized, parallel, double-blinded, multicentre controlled trial was conducted across eight Swedish hospitals. Eligible participants were individuals aged ≥ 18 years with acute cholecystitis lasting ≤ 7 days. Laparoscopic cholecystectomy was performed in the emergency setting as soon as local circumstances permitted. Random allocation to electrocautery or ultrasonic dissection was performed in a 1:1 ratio. The primary endpoint was the total complication rate, analysed using an intention-to-treat approach. The primary outcome was analysed using logistic generalized estimated equations. Patients, postoperative caregivers, and follow-up personnel were blinded to group assignment. Results From September 2019 to March 2023, 300 patients were enrolled and randomly assigned to electrocautery dissection (n = 148) and ultrasonic dissection (n = 152). No significant difference in complication rate was observed between the groups (risk difference [RD] 1.6%, 95% confidence interval [CI], − 7.2% to 10.4%, P = 0.720). No significant disparities in operating time, conversion rate, hospital stay or readmission rates between the groups were noted. Haemostatic agents were more frequently used in electrocautery dissection (RD 10.6%, 95% CI, 1.3% to 19.8%, P = 0.025). Conclusions Ultrasonic dissection and electrocautery dissection demonstrate comparable risks for complications in emergency surgery for patients with acute cholecystitis. Ultrasonic dissection is a viable alternative to electrocautery dissection or can be used as a complementary method in laparoscopic cholecystectomy for acute cholecystitis. Trial registration The trial was registered prior to conducting the research on http://clinical.trials.gov , NCT03014817.